Prevalência da coccidiose associada às características de manejo em caprinos de duas microrregiões maranhenses - SOUSA FILHO, José Gracione do Nascimento (2018)
Coccidiosis / Eimeriosis have become a serious obstacle to goat production, and knowledge of the dynamics of infection is of paramount importance to promote strategic and efficient control in a region. The objective of the study was to evaluate the prevalence of coccidiosis associated with management characteristics in goats from two Maranhenses Microregions. A total of 387 stool specimens were collected from 14 farms for stool examination (oocyst in stool - Oopg). Questionnaires were applied to characterize the food and sanitary management of the herds observed. After analysis of fecal matter, it was verified that the prevalence of positive samples for the presence of oocysts of Eimeria spp. was 71.58% (277/387, 95% CI 66.89-75.84). It was observed that animals over 6 months of age presented a positive load with 77.26% (214/315) in the stool oocysts count, and for animals less than 6 months old only 22.74% (63/72) of positivity for oocysts of Eimeria spp. It was observed that in the sex factor associated with infection there was a higher prevalence in females showing that 74.01% compared to 25.99% of males. It was identified seven species of Eimeria spp. in goats in the Chapadinha microregion: E. arloingi, E. christenseni, E.joichijevi, E. hirci, E. caprovina, E. apsheronica, and E. ninakohlyakirnovae. The results in relation to the characterization of the farms showed that all had a corral, 42.85% used suspended sheepfolds and 57.14% ground, 83% kept the animals free and 16% semi-stable. At feed type, 36% of the animals were in cultivated pasture, 36% pasture + concentrate and 29% in native pasture. Animals over six months of age become the largest oocyst dispersers for infection and reinfection of other individuals. Applications of management measures may reduce infections, such as periodic deworming of adult animals, especially females, may be a measure to reduce infections of young animals.